FAKTOR YANG MEMENGARUHI PARTISIPASI MASYARAKAT PADA PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KABUPATEN TULUNGAGUNG - Ayu Pandansari; Deva Fosterharoldas Swasto (Jendela Inovasi Daerah, 2026)
Slum settlements remain a crucial issue in Indonesia, where the Kota Tanpa Kumuh (KOTAKU) Program serves as a strategic community-based development initiative that emphasizes community participation as a key component of implementation. Differences in the characteristics of urban and rural communities may influence the level of community participation. This study aims to verify the factors affecting community participation in the implementation of the KOTAKU Program in Tulungagung Regency by comparing urban (kelurahan) and rural (desa) areas. This research employs a mixed-method approach combining quantitative and qualitative methods. Data were collected through questionnaires, interviews, and observations in Tertek Urban Village and Serut Village. Seven variables were analyzed, including external parties, willingness, ability, opportunity, community understanding, social climate, and environmental knowledge. The results indicate that all seven variables influence community participation and are present in both locations, although the dominant factors differ. Some variables function as strong or weak supporting factors, while others tend to act as inhibiting factors due to high dependency on external parties. The study recommends a deeper understanding of community characteristics to ensure that similar programs in the future are implemented in a more contextual and adaptive manner.